Quantum correlations and limit cycles in the driven-dissipative Heisenberg lattice - Owen, E. T.; Jin, Jiasen; Rossini, Davide; Fazio, Rosario; Hartmann, M. J. (New Journal of Physics, 2018)
Driven-dissipative quantum many-body systems have attracted increasing interest in recent years as they lead to novel classes of quantum many-body phenomena. In particular, mean-field calculations predict limit cycle phases, slow oscillations instead of stationary states, in the long-Time limit for a number of driven-dissipative quantum many-body systems. Using a cluster mean-field and a self-consistent Mori projector approach, we explore the persistence of such limit cycles as short range quantum correlations are taken into account in a driven-dissipative Heisenberg model.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Driven-dissipative systems; Limit cycles; Mean-field approaches; Nonlinear systems; Quantum magnets; Quantum many-body systems